Electrospun core–sheath PCL nanofibers loaded with nHA and simvastatin and their potential bone regeneration applications - Qian, Chenghui; Liu, Yubo; Chen, Si; Zhang, Chenyang; Chen, Xiaohong; Liu, Yuehua; Liu, Ping (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Drugs and biocompatible nanoparticles have raised significant potential in advancing the bone regeneration. Electrospinning technology enables the full realization of the value of drugs and nanoparticles. Methods: In this study, we have successfully fabricated core–sheath nanofibers solely composed of polycaprolactone (PCL) polymer. Simvastatin (SIM) was confined to the core of the nanofibers while nanohydroxyapatite (nHA) was loaded on the nanofiber surface. Results: All the prepared nanofibers exhibited a cylindrical micromorphology, and the core–sheath structure was exploited using a Transmission Electron Microscope. X-ray pattern results indicated that SIM was in an amorphous state within nanofibers, while Fourier Transform InfraRed spectroscopy showed excellent chemical compatibility among SIM, nHA, and PCL. The actual loading of nHA within the nanofiber was determined by a thermogravimetric test due to the high melting point of nHA. Core–sheath nanofibers could release SIM for 672 h, which was attributed to the core–sheath structure. Furthermore, nanofibers loaded with SIM or nHA had a positive impact on cell proliferation, with the core–sheath nanofibers displaying the most favorable cell proliferation behavior. Discussion: Such a synergistic facilitation strategy based on materials and nanostructure may encourage researchers to exploit new biomedical materials in future.